The regulation of non-point source pollution and risk preferences: An experimental approach - Camacho-Cuena, Eva; Requate, Till (Ecological economics, 2012)
Many environmental problems, notably arising from agriculture, can be classified as non-point source pollution problems. In this paper we present results of an experimental study on the performance of three mechanisms designed to deal with such problems: collective fining, random fining, and a tax-subsidy scheme. We find that the fining schemes induce under-abatement, a feature being enforced with experience. We further elicit the participants' risk attitude and show that the performance of collective fining is not affected by the subjects' risk preferences. Under a system based on random fining the performance of the mechanism worsens in the presence of risk seeking subjects. However, coordination on over-abatement under the tax-subsidy can be alleviated if subjects are risk averse.